Great river, wide land the Rio Grande through history. - Sperry, Armstrong (Macmillan, 1967)
A regional survey of the great natural resource, the Rio Grande River and Valley, shared by New Mexico, Texas, and Mexico. Describes its contribution to U.S. history, ecological and archeological importance, and role in the development of atomic science.